Kajian Penerapan Model Teologi Kontekstual - Handoyo Kusumahadi; Iskak Sugiyarto (INDO PUBLISHING, 2025)
This study analyzes the ministry practices and doctrines of JKI The Rock Church, a charismatic church that bases its activities on the direction of the Holy Spirit. This approach often generates controversy, particularly due to unique practices such as